(untitled) (Journal of the College of Basic Education, 2023)
Iraq, through its geographical location close to Iran, was influenced by the Babi call, as it was central and southern Iraq, especially in religious places, and it has beliefs in the reappearance of Imam Al-Mahdi (may God be pleased with him), in addition to the presence of the students of Sheikh Ahmed Al-Ahsa’i and Sayyid Kazem Al-Rashti who were preaching the imminent reappearance. These factors helped to spread The Babi call is among the religious circles, and the Bab’s supporters used to come to Iraq by visiting the holy shrines, as the letters of the neighborhood had a role in spreading the call there, specifically Mulla Ali al-Bistami and Qurat al-Ain, who had a prominent role in leading the call in Iraq because of the religious information they possess Eloquence and the power of influence on others, and I was able to run lessons for women in Karbala and Baghdad and worked to change customs and traditions. Qajar in dealing with such beliefs, as Mullah Ali Al-Bistami was imprisoned and then deported to the capital of the Ottoman Empire, while the fate of Qurat Al-Ain was house arrest in the house of the Mufti Baghdad and expelled it and those with it from Iraq. These beliefs were not welcomed and widely attracted by the classes of society because they brought new and unknown matters to them, so they were fought and their spread was limited.